Sosialisasi Keamanan Instalasi Listrik Pada Rumah Tinggal Sederhana - T. M. Azis Pandria; Edi Mawardi; Bambang Tripoli; Zakia Zakia (Universitas Teuku Umar, 2021)
The increasing use of electrical equipment has an impact on increasing the need for electrical power. This is not followed by the development of electrical installations in residential homes as required in PUIL. Conditions that occur in many communities including in Gampong Panggong, and held as one of the trigger factors for fires caused by electricity.The initial survey of the problem was conducted to get an overview and then held discussions with Gampong Panggong officials to formulate the existing problems.This method is used to solve existing problems.The follow-up is to socialize the security of electrical installations in simple residences. At the end of socialization, an evaluation of people's understanding of the material submitted. Devotional activities in the form of socialization of electricity use properly and correctly in accordance with PUIL to the community. The achievement of socialization goals is characterized by increasing public knowledge of electrical safety factors, the use of appropriate equipment SNI and efforts to avoid the risk of fire due to electricity. Lack of understanding of electricity use properly and correctly due to the lack of information obtained by the public.